Hemostatic Efficacy of EVARREST™, Fibrin Sealant Patch vs. TachoSil® in a Heparinized Swine Spleen Incision Model. (1st December 2014) - Matonick, John P.; Hammond, Jeffrey
ABSTRACT Background: First-generation single-component hemostats such as oxidized regenerated cellulose (ORC), fibrin, collagen, and gelatin have evolved into second and third generations of combination hemostats. Objective: This study compares two FDA approved products, EVARRESTTM, Fibrin Sealant Patch, a hemostat comprised of a matrix of nonwoven polyglactin 910 embedded in ORC coated with human fibrinogen and thrombin to TachoSil® medicated sponge, an equine collagen pad coated with human fibrinogen and thrombin. Materials and Methods: Swine were anticoagulated with heparin to 3X their baseline activated clotting time and a 15 mm long × 3 mm deep incision was made to create a consistent moderate bleeding pattern. Test material was then applied to the wound site and compressed manually for 3 min with just enough pressure to prevent continued bleeding. Hemostatic effectiveness was evaluated at 3 min and 10 min. Results: At 3 min, the hemostasis success rate was 86% in the EVARRESTTM group and 0% in the TachoSil® group, p < .0001. The overall success rate at 10 min was 100% with EVARRESTTM and 4% with TachoSil®, p < .0001. Adhesive failure, in which the test material did not stick to the tissue, occurred in 96% of TachoSil® sites. In contrast, 100% of the EVARRESTTM applications adhered to the test site. Conclusions: EVARRESTTM, Fibrin Sealant Patch demonstrated greater wound adhesion and more effective hemostasis than TachoSil®. Adhesive failure was the primary failure mode for TachoSil® in this model.